Control potential of Heterorhabditis amazonensis (Rhabditida: Heterorhabditidae) in avocado borer, Stenoma catenifer (Lepidoptera: Elachistidae) - Andaló, Vanessa; Batista de Alvarenga, Cleyton; Zampiroli, Renan; Silva de Faria, Lucas; Janoni Carvalho, Fábio; Naves, Naessa (Revista Ceres, 2025)
Stenoma catenifer is considered the main pest of avocado, making impossible to commercialize the infested fruits. This study was conducted with the objective of evaluating the potential of Heterorhabditis amazonensis MC01 in the field control of avocado borer, as well as the nematode release method. Two treatments were tested, namely: release of dead Tenebrio molitor infected with the nematode and hydraulic nematode spraying; hydraulic application of chemical insecticides was used as a control. The experiment was set up in a randomized complete block design with 15 replicates. The concentration of suspension distribution was 5,500 infective juveniles per m2. At the experimental area traps with sex pheromone were installed to capture adult males. The number of borer fruits was evaluated in the two central plants of each plot, sampling 4 fruits per plant. There was a reduction in the percentage of borer fruits from 15 days of application for all control methods. After the release of nematodes, the adult population was similar to the control, and it can be inferred that, even without chemical control, there was no increase in the number of adults. Thus, H. amazonensis was considered promising under field conditions, reducing the populations of S. catenifer, in all release methods.